2023
DOI: 10.3390/diagnostics13122039
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Histopathological Biomarkers in Fatal Cases of Coronavirus Disease: A Study on Lung Tissue

Ioana-Andreea Gheban-Roșca,
Bogdan-Alexandru Gheban,
Bogdan Pop
et al.

Abstract: We aimed to evaluate the primary lung postmortem macro- and microscopic biomarkers and factors associated with diffuse alveolar damage in patients with fatal coronavirus (COVID-19). We retrospectively analyzed lung tissue collected from autopsies performed in Cluj-Napoca, Romania, between April 2020 and April 2021 on patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We examined 79 patients with confirmed SARS-CoV-2 infection, ages 34 to 96 years, split into two groups using the cut-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…No statistically significant differences in comorbidities, age, or sex were associated with the presence or absence of DAD. Furthermore, we noted that most patients with DAD had interstitial pneumonia (72.5%), which was previously reported on hematoxylin and eosin staining [28].…”
Section: Discussionsupporting
confidence: 84%
“…No statistically significant differences in comorbidities, age, or sex were associated with the presence or absence of DAD. Furthermore, we noted that most patients with DAD had interstitial pneumonia (72.5%), which was previously reported on hematoxylin and eosin staining [28].…”
Section: Discussionsupporting
confidence: 84%
“…Being rich in B lymphocytes ( Figure 3 K), we consider that bronchitis/bronchiolitis is likely due to the influenza virus. Additionally, in our previous studies, we observed that COVID-19 infection generally does not produce intense histological inflammation in the bronchial structures [ 23 , 24 ]. The involvement of bronchial structures has been reported in infections with influenza, adenovirus, herpes, varicella-zoster, and respiratory syncytial virus [ 25 ].…”
Section: Discussionmentioning
confidence: 98%